Pretreatment of Small-for-Size Grafts In Vivo by γ-Aminobutyric Acid Receptor Regulation against Oxidative Stress-Induced Injury in Rat Split Orthotopic Liver Transplantation - Tomohide Hori; Shinji Uemoto; Lindsay B. Walden; Feng Chen; Ann-Marie T. Baine; Toshiyuki Hata; Justin H. Nguyen (International Journal of Hepatology)
Background. Graft pretreatment to limit postoperative damage has the advantage of overcoming a current issue in liver transplantation (LT). The strategic potential of graft pretreatment in vivo by a specific agonist for γ-aminobutyric acid receptor (GABAR) was investigated in the rat LT model with a small-for-size graft (SFSG). Methods. Recipient rats were divided into three groups according to donor treatments and recipient surgeries: (i) saline and laparotomy, (ii) saline and split orthotopic liver transplantation (SOLT) with 40%-SFSG, and (iii) GABAR agonist and SOLT with 40%-SFSG. Survival was evaluated. Blood and liver samples were collected 6 h after surgery. Immunohistological assessment for apoptotic induction and western blotting for 4-hydroxynonenal, ataxia-telangiectasia mutated kinase (ATM), histone H2AX, phosphatidylinositol-3 kinase (PI3K), Akt, and free radical scavenging enzymes were performed. Results. Pretreatment by GABAR showed improvement in survival, histopathological assessment, and biochemical tests. Apoptotic induction and oxidative stress were observed after SOLT with an SFSG, and this damage was limited by GABAR regulation. GABAR regulation appeared to reduce DNA damage via the ATM/H2AX pathway and to promote cell survival via the PI3K/Akt pathway. Conclusions. Pretreatment in vivo by GABAR regulation improves graft damage after SOLT with an SFSG. This strategy may be advantageous in LT.